Effects of wave-current interactions on sediment dynamics in Hangzhou Bay during Typhoon Mitag - Li, Li; Xu, Jiayang; Ren, Yihan; Wang, Xiao Hua; Xia, Yuezhang (Frontiers in Earth Science, 2022)
The hydrodynamics and sediment characteristics of muddy estuaries and coasts during typhoons are closely related to the geomorphic evolution, ecological environment, and economic development of coastal zones. Taking the macro-tidal turbid Hangzhou Bay (HZB) as an example, the sediment characteristics and effects of wave-current interactions on sediment dynamics during Typhoon Mitag were studied using a well-calibrated numerical model. The model considered tide-wave sediment interactions and the reconstructed typhoon wind field. Net sediment fluxes were controlled by residual currents and suspended sediment concentration (SSC). The combined interactions of currents and waves led to a high SSC during the typhoon. Under calm conditions, the impact of wave-current interactions was small, except for the combined bottom stresses. The combined bottom stress was the primary wave-current interaction that changed sediment resuspension and increased SSC, particularly in shallow waters or during storms. The advection term, which played an essential role in reducing SSC in HZB, mainly affected SSC by increasing the velocity. The wave dissipation term enhanced vertical mixing, which involved the vertical exchange of suspended sediment and currents. In the shallow waters of the southern bay, the wave dissipation term mostly led to decreased bottom stresses, increased currents, decreased SSC, and increased SSC in deep waters. The effects of form drag, wave radiation stress, and refraction terms on the suspended sediment dynamics were relatively small. These findings provide a theoretical foundation for the study of dynamic geomorphology in macrotidal estuaries.